Ultralight and flexible supercapacitor electrodes made from Ni(OH)2 nanosheets doped with Ag nanoparticle/3D graphene composite. Issue 27 (23rd February 2015) - Lan, Wei; Sun, Yaru; Chen, Youxin; Wang, Junya; Tang, Guomei; Dou, Wei; Su, Qing; Xie, Erqing
Abstract : Ag nanoparticle doped Ni(OH)2 nanosheets are deposited on flexible 3D graphene by a facile hydrothermal method. The electrode shows high specific capacitance with an increase of 23% and excellent rate capability. The electrode also has good cycle stability. Abstract : A composite of Ni(OH)2 nanosheets doped with Ag nanoparticle/3D graphene (Ag/Ni(OH)2 /3DG) was synthesized by a combination of chemical vapor deposition and a hydrothermal process. The Ag/Ni(OH)2 /3DG composite is light, flexible and has a high conductivity. It can be utilized directly for supercapacitor electrodes (including current collectors) without using binder materials or conductive agents. Doping the Ni(OH)2 nanosheets with Ag nanoparticles can improve the conductivity, which enhances the specific capacitance of the hybrid electrode accordingly. Electrochemical tests show a high specific capacitance of 2167 F g −1 scaled to the total mass of the electrodes at 10 A g −1 current density, a good rate capability and an excellent cycling performance of 98% capacitance retention over 1000 cycles at 25 A g −1 current.